2022
DOI: 10.1021/acs.biomac.2c00951
|View full text |Cite
|
Sign up to set email alerts
|

Binding Affinity of Concanavalin A to Native and Acid-Hydrolyzed Phytoglycogen Nanoparticles

Abstract: Phytoglycogen (PG) is a polysaccharide produced in the kernels of sweet corn as soft, highly branched, compact nanoparticles. Its tree-like or dendritic architecture, combined with a high-safety profile, makes PG nanoparticles attractive for use in biological applications, many of which rely on the association or binding of small biomolecules. We have developed a methodology to functionalize surface plasmon resonance (SPR) sensor surfaces with PG nanoparticles, and we demonstrate the utility of the PG-function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…simple and cost-effective method of obtaining phytoglycogen from maize, which involved dehulling, pH adjustment, and thermal treatment to obtain purified phytoglycogen nanoparticles containing less than 1% protein and more than 98.8% polysaccharide. Moreover, the very-high-purity phytoglycogen with <0.10% protein, <0.09% lipids, and <0.04% ash was obtained after microfiltration and ultrafiltration of the resulting solution, and has a hydrated number-average molecular weight of 34.5 × 10 6 g/mol with a Schultz polydispersity index of 0.26, and a particle radius of 21 nm (Charlesworth et al, 2022;Simmons et al, 2020). Wang, Liu, et al (2019) characterized the yields and structures of bacterial Gly extracted from Escherichia coli using four methods: TCA-precipitated hot water extraction; TCA-precipitated cold water extraction; hot KOH solution extraction; and cold water extraction using sucrose gradient density ultracentrifugation.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
See 3 more Smart Citations
“…simple and cost-effective method of obtaining phytoglycogen from maize, which involved dehulling, pH adjustment, and thermal treatment to obtain purified phytoglycogen nanoparticles containing less than 1% protein and more than 98.8% polysaccharide. Moreover, the very-high-purity phytoglycogen with <0.10% protein, <0.09% lipids, and <0.04% ash was obtained after microfiltration and ultrafiltration of the resulting solution, and has a hydrated number-average molecular weight of 34.5 × 10 6 g/mol with a Schultz polydispersity index of 0.26, and a particle radius of 21 nm (Charlesworth et al, 2022;Simmons et al, 2020). Wang, Liu, et al (2019) characterized the yields and structures of bacterial Gly extracted from Escherichia coli using four methods: TCA-precipitated hot water extraction; TCA-precipitated cold water extraction; hot KOH solution extraction; and cold water extraction using sucrose gradient density ultracentrifugation.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…The response depended on the concentration and molecular weight of the carbohydrates present, which could be used to create Gly-based biosensors or bioreactors. Recently, Charlesworth et al (2022) developed a methodology to functionalize surface plasmon resonance (SPR) sensor surfaces with phytoglycogen nanoparticles, which was used to characterize the binding affinity of the tetrameric ConA or bioactive molecules toward exploiting the novel bioactive delivery vehicle.…”
Section: (Continues)mentioning
confidence: 99%
See 2 more Smart Citations
“…Small angle neutron scattering (SANS) measurements of aqueous dispersions of PG particles showed that they consist of a large number (6.66 × 10 4 ) of glucose monomers that are bonded in a dendritic or tree-like architecture, with a dense core and the outer surface decorated with short, hair-like glucose chains containing an abundance of hydroxyl groups (Figure b) . This distinctive particle architecture gives rise to a strong interaction with water, and a direct relationship between the amount of sorbed water and the mechanical stiffness of the particles. These unique physical properties, coupled with its nontoxicity and digestibility, make PG attractive for applications involving the human body such as personal care, nutrition, and biomedicine. ,, …”
Section: Introductionmentioning
confidence: 99%